Photogearing as a concept for translation of precise motions at the nanoscale - Gerwien, Aaron; Gnannt, Frederik; Mayer, Peter; Dube, Henry (Nature Chemistry, 2022)
One of the major challenges for harnessing the true potential of functional nano-machinery is integrating and transmitting motion with great precision. Molecular gearing systems enable the integration of multiple motions in a correlated fashion to translate motions from one locality to another and to change their speed and direction. However, currently no powerful methods exist to implement active driving of gearing motions at the molecular scale. Here we present a light-fuelled molecular gearing system and demonstrate its superiority over passive thermally activated gearing. Translation of a 180° rotation into a 120° rotation is achieved while at the same time the direction of the rotation axis is shifted by 120°. Within such photogearing processes, precise motions at the nanoscale can be changed in direction and decelerated in a manner similar to macroscopic bevel-gear operations in an energy consuming way—a necessary prerequisite to employ gearing as an active component in future mechanical nano-systems. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-04-29